2021
DOI: 10.1002/nafm.10683
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Bottlenecks for Age‐0 Walleye in Northern Wisconsin Lakes

Abstract: Some northern Wisconsin lakes have shown declines in catches of age-0 Walleye Sander vitreus in standardized fall electrofishing sampling, suggesting that recruitment bottlenecks are occurring in the first several months of life. In 2016 and 2017, we sampled six lakes with declining trends in natural Walleye recruitment (D-NR lakes) and seven lakes with a history of sustained natural recruitment (S-NR lakes) to determine if timing of potential recruitment bottlenecks for age-0 Walleye were consistent among D-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 71 publications
(170 reference statements)
0
35
0
Order By: Relevance
“…Alternatively, in some lakes, Walleye recruitment declines may be caused by declines in Yellow Perch recruitment through direct interspecific interactions. Yellow Perch are both a prey item (Engel et al 2000;Gostiaux et al 2022) and prey buffer (Forney 1974(Forney , 1976 for juvenile Walleye. Walleye and Yellow Perch population dynamics may be strongly linked through predator-prey interactions, particularly when Yellow Perch are the main prey source for Walleye (Forney 1971;Mills et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, in some lakes, Walleye recruitment declines may be caused by declines in Yellow Perch recruitment through direct interspecific interactions. Yellow Perch are both a prey item (Engel et al 2000;Gostiaux et al 2022) and prey buffer (Forney 1974(Forney , 1976 for juvenile Walleye. Walleye and Yellow Perch population dynamics may be strongly linked through predator-prey interactions, particularly when Yellow Perch are the main prey source for Walleye (Forney 1971;Mills et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we classified Yellow Perch and Walleye recruitment into "successful" or "unsuccessful" recruitment years using estimates of relative abundance. Based on previous work, age-0 Walleye CPE > 6.2 fish/km in fall electrofishing was used to designate a Walleye year-class as successful (as in Hansen et al 2015aHansen et al , 2018Gostiaux et al 2022). However, no benchmark currently exists for Yellow Perch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, significant Walleye recruitment declines have occurred among formerly strong, naturally recruiting populations (Rypel et al 2018; Hansen et al 2019). Studies have identified juvenile recruitment as a major contributing mechanism for declines in adult stocks (Hansen et al 2015; Boehm 2016; Gostioux 2018). That said, there is a growing body of literature pointing to a myriad of factors inhibiting Walleye persistence in north temperate lakes, including aquatic invasive species (Hansen et al 2020), fish community interactions (Hansen et al 2015, 2017, 2018), water clarity (Hansen et al 2019), temperature (Hansen et al 2015, 2019), habitat loss (Carpenter et al 2017; Hansen et al 2020), and overharvest (Embke et al 2019) among others (see Raabe et al 2020 for review).…”
mentioning
confidence: 99%
“…Stocking to rehabilitate and support Wisconsin Walleye fisheries has yielded mixed success (Lawson et al 2022). Additionally, the importance of Yellow Perch as prey for larval Walleye in northern Wisconsin lakes (Gostiaux et al 2022) and indications of declining Yellow Perch populations in Minnesota (Bethke and Staples 2015) have led to increased efforts to sample and characterize Yellow Perch populations in both states (Brandt et al 2022;Holbrook et al 2022) and consideration of expanding standard sampling techniques (Holbrook et al 2022). While this research has helped to reduce the number of viable hypotheses for Walleye recruitment declines, the direct mechanisms have yet to be determined.…”
Section: Variable Observations and Knowledge Gapsmentioning
confidence: 99%